Segmentation and analysis of the glomerular basement membrane in renal biopsy samples using active contours: a pilot study. - Rangayyan RM; Kamenetsky I; Benediktsson H (Journal of Digital Imaging, 2010)
Some renal diseases cause changes in the structure of the glomerular basement membranes (GBM). Measurement of the thickness of the GBM can be performed on transmission electron microscopy (TEM) images of renal biopsy samples. Increased thickness of the GBM is observed in patients with diabetic nephropathy. Abnormally thin GBMs are associated with hematuria. We propose image processing methods for the detection and measurement of the GBM. The methods include edge detection, morphological image processing, active contour modeling, skeletonization, and statistical analysis of the width of the GBM. In the present pilot study, the methods were tested with 34 TEM images of six patients. The estimated mean and standard deviation of the GBM width for a patient with normal GBM were 348 ± 135 nm; those for a patient with thin GBMs due to hematuria were 227 ± 94 nm; and those for a patient with diabetic nephropathy were 1,152 ± 411 nm. Comparison with manual measurements by an experienced renal pathologist indicated low error in the range of 36 ± 11 nm.